Publishing Process of 3D Animated Short Movie "Barley Manusia Ikan" Using The Technique Of "Dynamic Water Simulations" - Akmalia, Nurul; Widiargo, Antonius Edi; Yurmama, Tri Fajar; Rahmayanti, Handika Dany; Ardiani, Septia (Jurnal Ilmiah Publipreneur, 2023)
The 3D short animation movie "Barley Manusia Ikan" takes place in Labuan Bajo’s Messa Island precisely. The 3D short animation movie 'Barley Manusia Ikan' is set on Messa Island in Labuan Bajo, it is one of the Indonesia's national tourist priority destinations. The movie tells about the beauty of the landscape, community activities as well as the anatomical and metabolic features of the Bajo tribe from Messah Island. The production process involves pre-production, production, and post-production stages. Pre-production includes creating the script, storyboarding, designing characters, creating voiceovers, and designing the environment/map. Production involves modeling characters, creating assets and properties, designing textures, rigging, animating, and creating 3D special effects. Post-production includes editing and compositing, adding sound effects and music, and final rendering. The Labuan Bajo islands' landscape is surrounded by the ocean. Therefore, the movie's production process requires a complex method, which includes dynamic simulation, such as water splash, wake, ripple, bubble and many more. The 3D effect simulation process requires several experiments, which are quite time-consuming. For instance, obtaining the most realistic results for a scene with a duration of 2.5 seconds (water splash) takes 50 minutes. The research resulted to a realistic-looking 3D animation movie with 3D dynamic visual effects of 7 minutes duration.